The influence of soccer match play on physiological and physical performance measures in soccer referees and assistant referees - Castillo, D.; Yanci, J.; Cámara, J.; Weston, M. (Journal of Sports Sciences, 2016)
The aim of this study was to quantify the acute impact of soccer match officiating on selected physiological and physical performance measures. Twenty-four officials from the Spanish National 3rd Division participated in this study. External global positioning system and internal (heart rate) load data were collected for each match official during 8 official matches. Pre- and post-matches, the referees were assessed for tympanic temperature, blood lactate, 15- and 30-m sprint speeds and unilateral (dominant and non-dominant legs) and bilateral vertical jump performances. For referees, the acute physiological and physical performance effects of officiating (post-match value minus pre-match value) were large increases in blood lactate (1.7 mmol/l; ±90% confidence limit, 0.9 mmol/l; effect size, ES = 4.35), small increases in 15-m sprint (0.09; ±0.04 s; ES = 0.53) and 30-m sprint speeds (0.14; ±0.08 s; ES = 0.39) and a small increase in non-dominant leg jump performance (2.1; ±1.4 cm; ES = 0.31). For assistant referees, there was a small decrease in tympanic temperature (-0.3°C; ±0.2°C; ES = -0.65) and small increases in blood lactate (0.4; ±0.3 mmol/l; ES = 0.66), 15-m sprint speed (0.06; ±0.04 s; ES = 0.47), 30-m sprint speed (0.11; ±0.16 s; ES = 0.49) and bilateral countermovement jump height (3.4; ±1.5 cm; ES = 0.45). Taken together, these data demonstrate that the physical demands of soccer officiating are sufficient to elicit increases in blood lactate and small decrements in sprint performance and, thereby, provide some evidence for match-related fatigue.